PENCIPTAAN HABITUS REMAJA PERKOTAAN DI KLUB MALAM SKY GARDEN, BADUNG - Agusman, Riko; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT This research aims to explain the process of habitus creation by urban teenagers at Sky Garden night club in Badung Regency. The background of this research is the great interest of urban teenagers, especially college students, to visit Sky Garden night club. This teenagers’ great interest to visit the night club is supported by facilities given by the club, like free entry and free drink. The participation of teenagers in clubbing world is also influenced by friends of the same age, family, taste, and is supported by fund owned. The social environment in the clubbing place is slowly adapted by teenagers and changes their habitus with/without recognition. The changes commonly occur in attitudes, behavior, habits, language, and fashion. The changes occurred as mentioned before may improve social relations, language development and fashion and for refreshing from the daily routine. Clubbing activities by teenagers generally do not interfere with the lecture. On the other hand, it can develop teenagers’ self-potentials and earn income. The process of habitus creation by urban teenagers in this research was analyzed by using the habitus theory by Pierre Bourdieu. Keyword: Habitus, Teenagers, Clubbing